Efficient pole-arc coefficients for maximum no load flux linkage in axial flux permanent magnet machines - Ferreira, Ângela P. (2012)
This paper presents a comprehensive study towards the determination of efficient pole-arc coefficients for axial flux permanent magnet (PM) machines, through investigation of the contribution of volume elements of PMs to the no load flux linkage. The proposed methodology involves the evaluation of flux linkage using a mathematical expression which integrates a function over the volume of PMs instead of the classical integration of the magnetic flux density over the coil surface. The process is implemented using 2D finite element (FE) analysis, and the results shows the pole-arc coefficients that maximize the ratio of the flux linkage over the PM volume is between 0.5 and 0.6.